Comparative pharmacoeconomic analysis schemes dosage of hormonal stimulation during in vitro fertilization - I. S. Krysanov; V. S. Krysanova; A. G. Tolkushin (Izdatelstvo OKI, 2018)
Purpose: Definition the scheme of hormonal stimulation, which is the most pharmacoeconomical founded. Methods: Pharmacoeconomic analysis was performed using the cost minimization analysis on the assumption of equal effectiveness compared schemes of hormonal stimulation, which was confirmed in the review of clinical trials and meta-analysis. To estimate the cost of drugs for ovulation induction we used registered VED rates and recommended in the instructions for medical use and the standard of care for infertility using assisted reproductive technologies dosing regimens. Results: The cost of the courses of drugs (1) corifollitropin a + ganirelix (32.9%), corifolhtropin a + ganirelix + follitropin (3 (67.1%) and (2) follitropin a + cetrorelix was 38 108.5 rub. and 47 102 rub., respectively. Cost saving of the budget by using the first scheme was 8 993.5 rub. for one course of in vitro fertilization. Conclusions: The scheme of hormonal stimulation using corifollitropin a is more pharmacoeconomical reasonable.